Exchange Rate Expectations : Survey of Survey Studies. (IMF Working Papers; Working Paper ;, 1990)
This paper presents a brief survey of the empirical literature on survey-based exchange rate expectations. The literature in general supports the presence of a non-zero risk premium and rejects the hypothesis of rational expectations. The crucial result is that, while short-run expectations tend to move away from some long-run 'normal' values, long-run expectations tend to regress toward them. If this nature of short-run expectations increases the volatility of exchange rate movements, there may be a basis for some official measure to minimize short-run exchange rate movements.